Funcionamiento familiar y bullying en estudiantes de Educación Secundaria de instituciones educativas públicas de Lima-Perú - Espinoza Núñez, Juan Manuel (2022)
The bullying is a problem that harms gravely the process of teaching learning at the classroom, as well as the existent social connections in her same, so much between companions like between students and professor. It can become manifest of different forms, since investigation is a complex phenomenon that cannot assume a very cause or present factor. This investigation examines the relation between the bullying and the family functioning, in 376 students' sign of secondary education of San Bartolo's and Pachacámac's districts. A designing is assumed not experimental, transeccional and correlacional. The utilized instruments were the Auto-Test Cisneros of School harassment to measure the variable bullying and Evaluación's Questionnaire of the Family Functioning to measure the family functioning. The more important result was to find a significant correlation of -, 989 between the family functioning and the bullying that leads to conclude that the students that have a good family functioning experience bullying's low level.